Noise-induced hearing loss and its determinants among workers in food supply, central supply and maintainance departments at Songklanagarind Hospital - T Pholchan; S Peeravud; S Chayarpham; P Tuntiseranee (Journal of Health Science and Medical Research (JHSMR), 2004)
Objective: To study the prevalence of noise-induced hearing loss (NIHL) and to investigate its determinant among workers Material and Methods: The study included 128 workers in food supply, central supply and maintainance departments at Songklanagarind Hospital during July to November 1998. History-taking, otologic evaluation and audiometry were performed as well as area sampling for noise level at each worksite. Results: The prevalence of NIHL was 28.1%, comprising registered NIHL 25% and NIHL 3.1%, while the prevalence of conductive hearing loss and sensorineural hearing loss from other unspecific cause were 3.1% and 11.7%, respectively. Noise beyond the standard of 85 dB(A) was reported among dish washing workers in the food supply department. From logistic regression analysis, factors showing statistically significant association with NIHL were male see and history of ever smoking but not history of sensorineural hearing loss among relatives, age of more than 40 years, department or duration of working in that department. Conclusion: NIHL was an occupational problem among workers in Songklanagarind Hospital and a hearing conservation program is urgently needed.